2009
DOI: 10.1002/ana.21840
|View full text |Cite
|
Sign up to set email alerts
|

Role of endogenous testosterone concentration in pediatric stroke

Abstract: Previous studies have indicated a male predominance in pediatric stroke. To elucidate this gender disparity, total testosterone concentration was measured in children with arterial ischemic stroke (AIS; n = 72), children with cerebral sinovenous thrombosis (CSVT; n = 52), and 109 healthy controls. Testosterone levels above the 90th percentile for age and gender were documented in 10 children with AIS (13.9%) and 10 with CSVT (19.2%), totaling 16.7% of patients with cerebral thromboembolism overall, as compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 19 publications
3
35
0
Order By: Relevance
“…Abnormal neurological status at discharge was documented in 43% of children in this study, further illustrating the serious nature of this disease. While long-term outcome data were not available in our study, these observations are consistent with reported rates of long-term neurological impairments and neurocognitive deficits in 40%–60% of survivors 3 5 8 12 15 16. Evaluation of risk factors for poor outcome or death identified coma as a risk factor for death and neurological sequelae, although this is only statistically significant for the latter group, probably because of the small number of deaths.…”
Section: Discussionsupporting
confidence: 90%
“…Abnormal neurological status at discharge was documented in 43% of children in this study, further illustrating the serious nature of this disease. While long-term outcome data were not available in our study, these observations are consistent with reported rates of long-term neurological impairments and neurocognitive deficits in 40%–60% of survivors 3 5 8 12 15 16. Evaluation of risk factors for poor outcome or death identified coma as a risk factor for death and neurological sequelae, although this is only statistically significant for the latter group, probably because of the small number of deaths.…”
Section: Discussionsupporting
confidence: 90%
“…Neonatal brain lesions due to SVT found on MRI corresponded with known drainage territories of dural venous sinuses 11 and were comparable to other reports, 11,26,27 as was the incidence of thalamic hemorrhage and intraventricular hemorrhage. 1,4,28 Deep white matter and basal ganglia are drained by the internal cerebral and basal veins of Rosenthal, which join to form the great vein of Galen, eventually draining into the straight sinus.…”
Section: Discussionsupporting
confidence: 88%
“…27 Children and neonates show elevated testosterone levels, which increases the odds of cerebral thromboembolism. 28 Cell death pathways in response to ischemia are also influenced by gender. 25 The majority of patients in our study had unilateral lesions in anterior circulation on the left side, consistent with populations in previous studies.…”
Section: Discussionmentioning
confidence: 99%